IMPLEMENTASI PMA NOMOR 30 TAHUN 2005 TENTANG WALI HAKIM - Muhammad Sirojudin Sidiq (LPPM STAI DARUSSALAM LAMPUNG, 2015)
A guardian is one of the foundations determining the marriage to be either legal or illegal, hence however the situation, the guardian has to be exist. If the parental guardians are not exist anymore, or unqualified to be a guardian, or mafqud, or not well-known addressed, or difficult to be called, so person who has a right to be a guardian in that marriage is magistrate guardian. Magistrate guardians according to Islam are people who have authority in the country they lead the society. According to PMA No. 30 Year 2005 about Magistrate Guardian, there is explained that magistrate guardian is the Head of sub-district KUA assigned by Ministry of Religion to be a guardian of a bride who does not have any guardians. When the Head of KUA is on business or not exist, the Head of Islamic Societal Guidance in act for the Head of Ministry of Religion in District assigns one of the Headmen in Sub-district or closest place to be the magistrate guardian in his place temporarily.